2016
DOI: 10.2134/jeq2015.03.0135
|View full text |Cite
|
Sign up to set email alerts
|

Improved Simulation of Edaphic and Manure Phosphorus Loss in SWAT

Abstract: Watershed models such as the Soil Water Assessment Tool (SWAT) and the Agricultural Policy Environmental EXtender (APEX) are widely used to assess the fate and transport of agricultural nutrient management practices on soluble and particulate phosphorus (P) loss in runoff. Soil P-cycling routines used in SWAT2012 revision 586, however, do not simulate the short-term effects of applying a concentrated source of soluble P, such as manure, to the soil surface where it is most vulnerable to runoff. We added a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 43 publications
(69 reference statements)
0
48
0
Order By: Relevance
“…This feedback loop guarantees a relatively rapid PSC and labile P increase under amendments. Thus, a dynamic PSC was necessary to maintain the equilibrium between different P pools (Collick et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This feedback loop guarantees a relatively rapid PSC and labile P increase under amendments. Thus, a dynamic PSC was necessary to maintain the equilibrium between different P pools (Collick et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Phosphorus in crop residues, soil, and applied amendments (i.e., manure and fertilizer) represents a consistent source of nonpoint pollution in surface runoff from agricultural lands (Bennett et al, 2001; Collick et al, 2016). The latter P source can overweigh all others when a large precipitation event follows closely after amendment application and water soluble forms of P are lost directly from the applied amendments (Withers et al, 2001).…”
mentioning
confidence: 99%
“…In contrast, APLE simulates P transformation and dissolution from a distinct surface layer of P using a set of empirically based equations. As a result, the amount of P vulnerable to runoff loss will generally be greater for APLE than TBET, potentially leading to greater predictions of P loss following manure application (Sen et al, 2012; Collick et al, 2016). Incorporating daily versions of the APLE manure P‐loss routines into SWAT (revision 586), Collick et al (2016) found that the new P routines better represented effects of different manure management practices on P losses at the small watershed scale (it is unclear when these modifications will be incorporated into TBET).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the amount of P vulnerable to runoff loss will generally be greater for APLE than TBET, potentially leading to greater predictions of P loss following manure application (Sen et al, 2012; Collick et al, 2016). Incorporating daily versions of the APLE manure P‐loss routines into SWAT (revision 586), Collick et al (2016) found that the new P routines better represented effects of different manure management practices on P losses at the small watershed scale (it is unclear when these modifications will be incorporated into TBET). Differences in how APLE and TBET simulate incidental P losses from surface‐applied manures, however, cannot entirely account for the differences we observed in predictions of DP loss between the two models, as we did not find a strong correlation between residuals in predicted DP loss and surface‐applied P rates (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, modeling different management practices such as tillage during periods of low rainfall can be compared to investigate methods to prevent stratification and reduce particulate P loss. Modeling with detailed weather data (e.g., to capture high‐intensity rainfall over a given time period) can identify climatic effects on soil P loss pathways (e.g., large rainfall periods corresponding to leaching events as is routinely used for nutrient management) (Collick et al, 2016; Sharpley et al, 2017; Verburg et al, 2018). Other management options such as the 4R Nutrient Stewardship system (Johnston and Bruulsema, 2014), changes to irrigation schedules, cover crops during fallow periods, and timing and depth of fertilizer application should also be tested prior to adopting new practices.…”
Section: Research Gap 1: Agricultural Systems Modeling To Improve Phomentioning
confidence: 99%